Effect of Protein Binding on Unbound Atazanavir and Darunavir Cerebrospinal Fluid Concentrations - Delille, Cecile A. (J Clin Pharmacol, 2014)
HIV-1 protease inhibitors (PIs) exhibit different protein binding affinities and achieve variable plasma and tissue concentrations. Degree of plasma protein binding may impact central nervous system penetration. This cross-sectional study assessed cerebrospinal fluid (CSF) unbound PI concentrations, HIV-1 RNA, and neopterin levels in subjects receiving either ritonavir-boosted darunavir (DRV), 95% plasma protein bound, or atazanavir (ATV), 86% bound. Unbound PI trough concentrations were measured using rapid equilibrium dialysis and liquid chromatography/tandem mass spectrometry. Plasma and CSF HIV-1 RNA and neopterin were measured by Ampliprep/COBAS® Taqman® 2.0 assay (Roche) and enzyme-linked immunosorbent assay (ALPCO), respectively. CSF/plasma unbound drug concentration ratio was higher for ATV, 0.09 [95% confidence interval (CI) 0.06–0.12] than DRV, 0.04 (95%CI 0.03–0.06). Unbound CSF concentrations were lower than protein adjusted wild-type inhibitory concentration-50 (IC(50)) in all ATV and 1 DRV-treated subjects (P < 0.001). CSF HIV-1 RNA was detected in 2/15 ATV and 4/15 DRV subjects (P = 0.65). CSF neopterin levels were low and similar between arms. ATV relative to DRV had higher CSF/plasma unbound drug ratio. Low CSF HIV-1 RNA and neopterin suggest that both regimens resulted in CSF virologic suppression and controlled inflammation.